Pihak yang Berperan dalam Implementasi Pendidikan Inklusi - Putri, Ananta; Zikri, Habib; Mustika, Dea (TSAQOFAH, 2024)
Elementary schools with inclusive education programs are a challenge for school principals and teachers in educational institutions. Inclusive education in elementary schools needs to receive more attention considering that elementary school students still need intensive attention from educators plus attendance students with special needs, of course it is not easy to achieve learning goals. The aim of this research was to see and describe the phenomena that occurred during implementation inclusive education in elementary schools. This research uses descriptive methods to analyze actual data and objects in the implementation of inclusive education in elementary schools. teachers, parents and the community need to work together in implementation to be able to provide services appropriate for students in general and children with special needs as an effort to improve quality educational services in elementary schools.